2014
DOI: 10.1155/2014/970468
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Filler Content on the Performance of Epoxy/PTW Composites

Abstract: This paper presents the mechanical and tribological characteristics of potassium titanate whisker (PTW) reinforced epoxy composites. The effect of various test variables and material parameters on the friction and wear behavior of epoxy/PTW composites has been studied systematically. Tribological tests were conducted on a pin-on-disc apparatus under dry sliding conditions. Addition of PTW was found to improve the wear resistance of the composites and 15 wt% PTW filled epoxy exhibited lowest specific wear rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(47 citation statements)
references
References 32 publications
2
43
0
2
Order By: Relevance
“…This results in strong covalent bonds between the E‐glass and its coating and, thus, in improved mechanical properties. Furthermore, a strong interface prevents the peel‐off of the coating during processing at elevated temperatures and shear conditions, which has been reported to occur for weak matrix–filler interfaces , such as the combination of A‐glass and the aminosilane coating. Moreover, E‐glass exhibits a smaller surface contact angle with water than A‐glass , which is an indication for a more reactive surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This results in strong covalent bonds between the E‐glass and its coating and, thus, in improved mechanical properties. Furthermore, a strong interface prevents the peel‐off of the coating during processing at elevated temperatures and shear conditions, which has been reported to occur for weak matrix–filler interfaces , such as the combination of A‐glass and the aminosilane coating. Moreover, E‐glass exhibits a smaller surface contact angle with water than A‐glass , which is an indication for a more reactive surface.…”
Section: Resultsmentioning
confidence: 99%
“…a) and with the weak interfacial bonding between the coating and the A‐glass (see “ Tensile Properties ”). During shear deformation, the spheres can detach from the coating , resulting in an increased tendency to agglomerate and, hence, an elevated viscosity at low shear rates . Contrary to this, the compound PP/MA/E‐C reaches a Newtonian plateau for frequencies lower than 50 rad s −1 .…”
Section: Resultsmentioning
confidence: 99%
“…The heterogeneity of thick-walled castings structure may be yet another reason for lower impact strength [27] . The comparison of the impact strength and DMTA results confirmed that high aspect ratio filler particles improved stiffness in a composite; however, they caused increased stress concentration in the polymer matrix near particle edges under impact loads [38] . The impact strength describes the ability of a material to resist fracture under stress applied at high speed.…”
Section: Charpy Impact Strength and Shore D Hardnessmentioning
confidence: 65%
“…In this study, specific wear rate decreases with increase in normal load for all the composites. [25][26][27] Figure 5 represents the variation of specific wear rate of BFS particulate-filled needle-punched nonwoven polyester fabric reinforced epoxy composites with different sliding [26][27][28][29] In the current study, with the increase in sliding velocity the abrasive grit flow rate in the slurry and the energy level of impinging particles significantly increased. [22] In the initial phase of abrasion, the stress produced by abrasive slurry is sufficient to facilitate failure of resin reach top surface and which leads to high material removal rate.…”
Section: Steady-state Specific Wearmentioning
confidence: 94%
“…Reduction in specific wear rate with the increase in load has been reported by different past researchers for fiber-reinforced polymer composites. [25][26][27] Figure 5 represents the variation of specific wear rate of BFS particulate-filled needle-punched nonwoven polyester fabric reinforced epoxy composites with different sliding velocity under steady-state conditions (at normal load of 10 N, at sliding distance of 600 m and silica sand size of 300 μm). The unfilled composites display highest specific wear rate with a value of 41.07 mm 3 /N-m and the BFS-filled composites show the lowest value at 4.90 mm 3 /N-m.…”
Section: Steady-state Specific Wearmentioning
confidence: 99%